The effect of tillage systems and dosages of cow manure on weed and soybeans yield (Glycine max, Merrill) - Husni Thamrin Sebayang; Siti Fatimah (Journal of Degraded and Mining Lands Management, 2019)
A field experiment to elucidate the effect of tillage systems and dosages of cow manure on weed and soybeans yield (Glycine max, Merrill) was conducted at the Agrotechno Park of the University of Brawijaya in Jatikerto, Malang, from May to July 2017. The experiment used a split-plot design with 3 replications. The main plot was the tillage systems, with 3 levels: T0= No-tillage, T1= Minimum tillage, and T2 = Conventional tillage. The subplot was the dosages of cow manure, with 3 levels: P1= 2.5 t cow manure/ha, P2 = 5 t cow manure/ha, and P3 = 7.5 t cow manure/ha. Results of experiment showed that dry weight of weed was higher at no-tillage systems and at dosages of 7.5 t cow manure/ha. Growth and yield of soybean were lower at no-tillage compared with conventional tillage systems. Application of cow manure with dosages of 5 t/ha and 7.5 t/ha was better than 2.5 t/ha for growth and yield of soybean.